Forensic Accounting and Fraud Detection in Two Decades: A Bibliometric Study - Claresta Sharon Eunike Lario; Abdul Rohman (Jurnal Akuntansi dan Perpajakan, 2025)
This study aims to map the development of research in forensic accounting and fraud detection over the past two decades, covering the period from 2002 to 2024, through a bibliometric approach applied to 202 documents obtained from the Scopus database. Using RStudio and Biblioshiny, the study identifies publication trends, thematic developments, and patterns of international collaboration. The results reveal a significant upward trend in publications, with an average annual growth rate of 15.76%, reflecting the growing academic interest in fraud-related research. The United States emerged as the dominant contributor with strong domestic publication output, while international collaboration remained relatively limited. The most frequently appearing themes include “fraud,” “crime,” and “computer crime,” whereas topics such as “computer forensics” and “law-related legislation” remain underexplored but present promising opportunities for future research. The motivation behind this study lies in the increasing digital risks, global financial complexity, and the need for accountability and transparency in detecting and preventing fraudulent practices. This research contributes to the literature by providing a structured overview of the thematic landscape, identifying research gaps, and encouraging the expansion of multidisciplinary and cross-country collaboration. However, the study is limited to Scopus-indexed publications, excluding other databases such as Web of Science and Google Scholar, which may restrict the comprehensiveness of the findings. The implications highlight the importance of integrating bibliometric and qualitative approaches to gain a deeper understanding of forensic accounting’s evolving role in fraud prevention. Overall, the study underscores the strategic importance of forensic accounting as a global discipline that bridges financial integrity, legal compliance, and digital resilience.